CAMPUR KODE PADA TEKS PIDATO SISWA KELAS IX SMP PONDOK PESANTREN ASSALAM PONTIANAK - Adi Supriadi; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThe students’ writing that became the subject of research is the form of speech text. Students of Junior High School at Pontianak Assalam Islamic Boarding School, in their learning, learn a lot using other languages besides Indonesian. This research was conducted to see and describe the form of code mixing and the factors that cause code mixing in speech texts made by students. The method used in this research is descriptive method with the form of this research is qualitative, and use a sociolinguistic approach. The theory used in this research is the theory of language contact, bilingualism and code mixing. The results of the analysis of this study were obtained 80 data in the form of code mixing. There are 73 data in the form of mixed Arabic code and 7 data in the form of mixed Malay code.The factors causing the occurrence of code mixing in the students' speech texts are as follows. First, the factor of leisure and habit of speakers in informal situations. Second, the desire factor to explain and interpret.Keywords: sociolinguistics, code mixingAbstractThe students’ writing that became the subject of research is the form of speech text. Students of Junior High School at Pontianak Assalam Islamic Boarding School, in their learning, learn a lot using other languages besides Indonesian. This research was conducted to see and describe the form of code mixing and the factors that cause code mixing in speech texts made by students. The method used in this research is descriptive method with the form of this research is qualitative, and use a sociolinguistic approach. The theory used in this research is the theory of language contact, bilingualism and code mixing. The results of the analysis of this study were obtained 80 data in the form of code mixing. There are 73 data in the form of mixed Arabic code and 7 data in the form of mixed Malay code.The factors causing the occurrence of code mixing in the students' speech texts are as follows. First, the factor of leisure and habit of speakers in informal situations. Second, the desire factor to explain and interpret. Keywords: sociolinguistics, code mixing